2013
DOI: 10.1117/1.jbo.18.5.050901
|View full text |Cite
|
Sign up to set email alerts
|

Review of speckle and phase variance optical coherence tomography to visualize microvascular networks

Abstract: Abstract. High-resolution mapping of microvasculature has been applied to diverse body systems, including the retinal and choroidal vasculature, cardiac vasculature, the central nervous system, and various tumor models. Many imaging techniques have been developed to address specific research questions, and each has its own merits and drawbacks. Understanding, optimization, and proper implementation of these imaging techniques can significantly improve the data obtained along the spectrum of unique research pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
164
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(165 citation statements)
references
References 84 publications
0
164
0
1
Order By: Relevance
“…As a result, it is possible that the effects of speckle might be absorbed into our formula, due to the fact that we used a higher order model. More recently, Mahmud et al reported in a review article on OCT speckle variance that OCT intensity follows Gaussian distribution in solid tissues, while it changes to Rayleigh distribution in fluids [43]. It is worth noting that both these two distributions are the special cases of Rice distribution ( v  leads to Gaussian distribution; and v  leads to Rayleigh distribution).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is possible that the effects of speckle might be absorbed into our formula, due to the fact that we used a higher order model. More recently, Mahmud et al reported in a review article on OCT speckle variance that OCT intensity follows Gaussian distribution in solid tissues, while it changes to Rayleigh distribution in fluids [43]. It is worth noting that both these two distributions are the special cases of Rice distribution ( v  leads to Gaussian distribution; and v  leads to Rayleigh distribution).…”
Section: Discussionmentioning
confidence: 99%
“…136 As mentioned before, it is possible to observe decorrelation or variance of phase, 137,138 speckle, 139,140 or the full complex signal. 141 An important factor, apart from the time interval, is the oversampling ratio, which is the number of A-scans per spot size of the scanning beam.…”
Section: Label-free Optical Angiographymentioning
confidence: 99%
“…The tissue was segmented in each structural (OCT magnitude) image by applying edge-detection to determine the tissue surface and an intensity threshold to exclude noise due to signal fall-off in depth. The segmented tissue mask was first applied to the speckle variance maps, which were then median filtered and de-shadowed using a stepdown exponential filter [54]. Next, bulk motion artifacts were minimized by plotting the average speckle variance for each B-scan in the volume (Fig.…”
Section: Swept-source Optical Coherence Tomographymentioning
confidence: 99%